Enhancing the Growth Rate, Biochemical Blood Indices, and Antioxidative Capacity of Broilers by Including Aloe vera Gel in Drinking Water - Amber, Khairy; Nofel, Reayd; Ghanem, Reda; Sayed, Samy; Farag, Soha A.; Shukry, Mustafa; Dawood, Mahmoud A. O. (Frontiers in Veterinary Science, 2021)
Phytogenic herbal extracts received considerable attention in the broilers industry as friendly alternative substitutes to antibiotics. These additives can be included in the food or drinking water to enhance birds' growth rate and well-being. Hence, the current investigation examined the effect of including Aloe vera gel in drinking water on the growth rate, biochemical blood indices, and broilers' antioxidative capacity. Cobb 500 broiler chicks (n = 120), 1 day old of initial weight = 48.6 ± 1.65 g, were divided into three treatments where the control group was fed the basal diet without including Aloe vera gel in drinking water. The second and third groups were fed the basal diet, and Aloe vera gel was included in drinking water at 1 and 1.5%, respectively. The final body weight, weight gain, daily weight gain, and feed conversion ratio were significantly improved in birds that received drinking water with Aloe vera gel at 1.5% compared to the control and 1% groups (P ≤ 0.05). The kidney (creatinine and urea) and liver (ALT and AST) function indices of broilers that received drinking water with or without Aloe vera gel showed no significant differences with the control group (P ≥ 0.05). The blood total protein and albumin had higher values in birds that received drinking water with 1.5% Aloe vera gel than the control (P ≤ 0.05). The total blood cholesterol, triglycerides, and LDL levels were significantly decreased in the group of birds that received 1.5% Aloe vera gel in drinking water (P ≤ 0.05). The HDL level was higher in birds that received drinking water with 1.5% Aloe vera gel than the control (P ≤ 0.05). The total antioxidative capacity (TAC) and glutathione peroxidase (GPX) showed higher activity in the group of birds that received 1.5% Aloe vera gel while the level of malondialdehyde (MDA) was lower in birds that received drinking water with 1.5% Aloe vera gel than the control (P ≤ 0.05). In summary, including Aloe vera gel in drinking water enhanced the growth rate, biochemical blood indices, and broilers' antioxidative capacity.